Delayed school start times and motor vehicle accidents: a need for further inquiry - Barlaan, Devin R. (J Clin Sleep Med, 2020)
Barlaan DR, Sinor K, Cromer LD. Delayed school start times and motor vehicle accidents: a need for further inquiry. J Clin Sleep Med. 2020;16(9):1627.